The effect of dual-task training in older adults with total hip arthroplasty: a randomized controlled trial - İsmail Uysal; Fatih Özden; Mustafa Yalçın; Emir İbrahim Işık; Zübeyir Sarı (BMC Musculoskeletal Disorders)
Abstract Background No other study has addressed the effectiveness of dual-task training in the postoperative period of total hip arthroplasty (THA). This study investigated the efficacy of dual-task training in older adults with THA. Methods Patients were randomized into the control group (CG) (n = 14) and intervention group (IG) (n = 14). Patients in the CG received the usual post-operative rehabilitation for 8 weeks. IG-group received 8-week dual-task training in addition to the program given to the CG. Visual Analog Scale (VAS), Harris Hip Score (HHS), Mini-Mental Status Examination (MMSE), Dual Task Questionnaire (DTQ), Cognitive Timed Up and Go Test (cTUG), Lower Extremity Motor Coordination Test (LEMOCOT), 4 m Walking Speed (4MWS), Five Times Sit to Stand Test (FTSST), Activity Specific Balance Confidence Scale (ABC) were used to assess the patients after the sixth week of the surgery and after the two months of the initial assessment. Results All evaluated parameters of the intervention group (VAS, HHS, MMSE, DTQ, cTUG, LEMOCOT, 4MWS, FTSST, and ABC) improved significantly after the intervention. Also, significant improvement was seen in all scores (VAS, HHS, MMSE, DTQ, cTUG, LEMOCOT, 4MWS, FTSST, and ABC) except for HHS-pain (0.059) and HHS-deformity (0.157) (p < 0.05) for the control group. The score change of the intervention group was significantly better for all evaluated parameters (VAS, HHS, MMSE, DTQ, LEMOCOT, 4MWS, FTSST, and ABC) (p < 0.05), except cTUG. All parameters of the intervention group were clinically meaningful regarding MCID values, except HHS-pain, HHS-living activities, and cTUG score change. Besides, HHS-pain, HHS-living activities, HHS-deformity, MMSE, LEMOCOT, FTSST, and ABC score change was not meaningful clinically. Conclusion An eight-week dual-task training provides better results on pain, function, dual-task performance, motor coordination, gait, and balance than usual rehabilitation in patients after 6-weeks of THA. The results showed that patients after THA achieved improvements with gains in motor-cognitive function. Trial Registration The study protocol was registered to “clinicaltrials.gov” (Registration Date: 19/08/2023, Clinical Trial Number: NCT06009419|| https://clinicaltrials.gov/study/NCT06009419 ).